Analisis Kesalahan Berbahasa (Tulis) Pemelajar BIPA Level 7 dalam Pembuatan Karya Ilmiah (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
This study aims to describe written language errors of level 7 BIPA students in writing scientific papers, including errors in (1) conjunctions, (2) capital letters, (3) puntuations, and (4) sentences structure. The data used in this study were three BIPA level 7 scientific papers. The method used was descriptive-qualitative. Data analysis was carried out by (1) note things that are aspects of language errors, (2) classify language errors into certain groups, and (3) describe those language errors. The result of the study show that in the scientific papers of BIPA level 7 students there are still many errors, including errors in using conjunctions at the beginning of sentences, inaccuracies in the use of capital letters which are often placed in the middle of sentences, inaccuracies in the use of comma and full stop punctuation, and sentence ineffectiveness triggered by structural interference sentences in foreign languages, redudant words, and incomplete sentence patterns.